2004
DOI: 10.1128/jvi.78.16.8746-8752.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Rabies Virus Forms Different Kinds of Fusion Machines with Different pH Thresholds for Fusion

Abstract: Fusion of rabies virus with membranes is triggered at a low pH and is mediated by a viral glycoprotein (G).Fusion of rabies virus with liposomes was monitored by using a lipid mixing assay based on fluorescence resonance energy transfer. Fusion was detected below pH 6.4, and its extent increased with H ؉ concentrations to be maximal around pH 6.15. The origin of the partial fusion activity of rabies virus under suboptimal pH conditions (i.e., between pH 6.15 and 6.4) was investigated. We demonstrate unambiguou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…This is in contrast to mammalian IFITM3, which can restrict VSV replication (5,7,12,13,38,44). IAV requires a pH of approximately 5.0 to 5.7 for membrane fusion, whereas VSV requires a less acidic pH of 6 (46)(47)(48)(49). The sites of fusion of viral and host membranes for IAV and VSV correspond to late endosomes/lysosomes and early endosomes, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…This is in contrast to mammalian IFITM3, which can restrict VSV replication (5,7,12,13,38,44). IAV requires a pH of approximately 5.0 to 5.7 for membrane fusion, whereas VSV requires a less acidic pH of 6 (46)(47)(48)(49). The sites of fusion of viral and host membranes for IAV and VSV correspond to late endosomes/lysosomes and early endosomes, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…This would suggest that the A117F poisoning of fusion may require intertrimer interactions. For rabies virus, it has been suggested that the refolding of as many as 16 trimers are required to drive membrane fusion (11,12,32). If a similarly high threshold is required for VSIV G, this may necessitate a significant number of A117F homotrimers to poison wild-type fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Like other rhabdoviruses, RABV gains access to the cellular interior by endocytosis and subsequent low pH-dependent fusion (5)(6)(7). Electron micrographs of viral particles in vesicles with electron-dense coats suggest that clathrin-coated pits mediate the uptake of RABV in both neuronal and nonneuronal cells (8,9).…”
mentioning
confidence: 99%